2013
DOI: 10.1093/infdis/jit361
|View full text |Cite
|
Sign up to set email alerts
|

Declining Genital Warts in Young Women in England Associated With HPV 16/18 Vaccination: An Ecological Study

Abstract: Background. Diagnoses of genital warts (GW) in genitourinary medicine (GUM) clinics have been increasing in England for many years. In 2008, an HPV immunization program began with a bivalent vaccine (Cervarix). This was expected to markedly reduce infections and disease due to human papillomavirus (HPV) 16/18 but not HPV 6/11 infections or disease. However, from 2009 to 2011 there were decreases in reported diagnoses of GW in young females at GUM clinics.Methods. Using data from GUM clinics and a sample of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 14 publications
4
60
0
1
Order By: Relevance
“…6 Data from Australia, the United States and the United Kingdom have shown that the vaccine is effective, with population level reductions in rates of genital warts, HPV and cervical cancer lesions. [7][8][9][10] Recent data from a populationbased study in the US, where HPV vaccine uptake has been <40%, found a reduction in HPV vaccine-type prevalence from 11.5% to 5.1% pre-and post-vaccine, respectively. 11 In Canada, between 2007 and 2009 all provinces and territories launched school-based HPV vaccine programs.…”
mentioning
confidence: 99%
“…6 Data from Australia, the United States and the United Kingdom have shown that the vaccine is effective, with population level reductions in rates of genital warts, HPV and cervical cancer lesions. [7][8][9][10] Recent data from a populationbased study in the US, where HPV vaccine uptake has been <40%, found a reduction in HPV vaccine-type prevalence from 11.5% to 5.1% pre-and post-vaccine, respectively. 11 In Canada, between 2007 and 2009 all provinces and territories launched school-based HPV vaccine programs.…”
mentioning
confidence: 99%
“…(21,22,73) This additional cross-protection against these low-risk HPV types was not included in our model and therefore the current results are likely to be a conservative estimate of the relative effectiveness of AS04-HPV-16/18v versus 4vHPV.…”
Section: Discussionmentioning
confidence: 99%
“…(9, 10) Cost of screening (SGD [15][16][17][18][19][20][21][22][23][24] is paid out of pocket, except for low-income citizens aged above 40 years, who have been fully subsidised since 2014. (11) Opportunistic screening is sometimes also provided for free through charitable organisations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, where 4vHPV coverage of the target female population has been high, a parallel reduction in genital warts has been observed in heterosexual males: a consequence of herd protection [15]. Surprisingly, decreases in the rates of genital wart diagnoses among vaccine-eligible females and same-aged males has been observed in England following 2vHPV vaccination [16]. Moderate 2vHPV vaccine efficacy against low-risk HPV types, through cross protection or cell-mediated immunity, may help to explain this observation [17].…”
Section: Hpv Clinical Vaccine Trialsmentioning
confidence: 99%